Antioxidant activity, anti-tyrosinase activity, and lipstick pigments of Oryza sativa Linn. and Carissa carandas Linn. extracts - Thitiporn Anunthawan, Thipwarin Rimlumduan (Journal of Applied Pharmaceutical Science, 2023)
Oryza sativa Linn. and Carissa carandas Linn extracts are composed of phenolic and flavonoid contents. Oryza sativa Linn. extract had antioxidant activities at 36.07 ± 5.71 mg Trolox (TE)/g dry weight (DW), 26.14 ± 4.43 mg TE/g DW, and 50.08 ± 1.54 mM TE/g DW in 2,2-diphenyl-1-picrylhydradzyl (DPPH), 2,2’-azino-bis(3- ethylbenzothiazoline-6-sulfonic acid (ABTS), and ferric-reducing antioxidant power (FRAP) assays, respectively. For C. carandas Linn., the extract had antioxidant activities at 41.53 ± 1.77 mg TE/g DW, 38.44 ± 4.39 mg TE/ g DW, and 109.18 ± 25.07 mM TE/g DW in DPPH, ABTS, and FRAP assays, respectively. The O. sativa Linn. extract could inhibit the tyrosinase at 45.70% ± 11.76%, which was higher than the C. carandas Linn. extract (36.90% ± 5.83%) at the same concentration (0.10 mg/ml). All gel lipstick formulas retained antioxidant and anti-tyrosinase activities. In the sensory test, the overall acceptability, color, and odor of gel lipsticks, which had C. carandas Linn. extract added, had the higher scores, suggesting a proper pigment in a darker color lipstick. However, the spreadability, flakiness, and color stability of all formulas should be further studied for better lipstick quality.
Keywords: Gel lipstick, Oryza sativa Linn., Carissa carandas Linn., anti-tyrosinase activity, antiox